A combined interval-valued ELECTRE TRI and TOPSIS approach for solving the storage location assignment problem. (September 2019) - Micale, R.; La Fata, C.M.; La Scalia, G.
Highlights: Design of a Multi-Criteria Decision Making approach to the Storage Location Assignment Problem in a 3D space. Interval-based formulation of ELECTRE TRI and TOPSIS to deal with uncertain input data. Design and implementation of a re-assignment procedure to ensure the occupation of the best storage locations. Abstract: Efficiency and effectiveness of logistic activities, in general, and of distribution networks, in particular, are largely influenced by the way warehouses operate as nodes of these networks. In recent years, warehouse management has undergone major changes due to the increase of e-commerce and competition in time-reduction. Despite that, logistic costs of warehouse processes (e.g. receiving, storage, order picking and shipping, etc.) are still often high. Referring to the order picking process, related activities may be optimized by a proper assignment of products to storage locations. In the literature, this problem is known as Storage Location Assignment Problem (SLAP). Due to the multi-criteria nature of SLAP, a combined ELECTRE TRI and TOPSIS based approach under an uncertain environment is designed in the present paper. Aiming at properly dealing with the uncertainty of the decision process, an interval extension of both ELECTRE TRI and TOPSIS is proposed. Therefore, ELECTRE TRI is firstly used to assign products to shelf levels whereas TOPSIS is afterwards applied to determine their storage locations within every level rather than using a random assignment policy. The whole methodology has been designed in cooperation with a Sicilian company that provides logistic services all over the Italian territory.